2016
DOI: 10.1111/sms.12660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of submaximal and supramaximal interval training on determinants of endurance performance in endurance athletes

Abstract: We compared the effects of submaximal and supramaximal cycling interval training on determinants of exercise performance in moderately endurance-trained men. Maximal oxygen consumption (VO ), peak power output (P ), and peak and mean anaerobic power were measured before and after 6 weeks (3 sessions/week) of submaximal (85% maximal aerobic power [MP], HIIT , n = 8) or supramaximal (115% MP, HIIT , n = 9) interval training to exhaustion in moderately endurance-trained men. High-intensity training volume was 47%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 32 publications
4
42
0
Order By: Relevance
“…For more detail and interpretation of these results on gas exchange analysis during this maximal cycling protocol, refer to Paquette et al. ().…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…For more detail and interpretation of these results on gas exchange analysis during this maximal cycling protocol, refer to Paquette et al. ().…”
Section: Methodsmentioning
confidence: 93%
“…Maximal V O 2 was defined as the highest 30-sec averaged V O 2 , concurrent with a RER ≥ 1.15. For more detail and interpretation of these results on gas exchange analysis during this maximal cycling protocol, refer to Paquette et al (2017).…”
Section: Maximal Oxygen Consumption (V̇o 2max )mentioning
confidence: 99%
“…VO2max was defined as the highest 30 s averaged VO2 concurrent with a RER ³ 1.15 (Paquette et al, 2017).…”
Section: Maximal Oxygen Consumptionmentioning
confidence: 99%
“…All participants were free from any diagnosed medical conditions. A variety of endurance sports were undertaken by the participants including road cycling (n = 9), triathlon (n = 7), mountain biking (n = 2) and cross-country skiing (n = 1) (29).…”
Section: Participantsmentioning
confidence: 99%
“…Different HIIT protocols are used by athletes, such as submaximal training below maximal oxygen consumption (VO2max), training at VO2max and supramaximal training (power output above VO2max). Our research group compared two of these HIIT protocols, and recently reported that endurance-trained men performing 6 weeks of submaximal (85% maximal aerobic power) and supramaximal (115% maximal aerobic power) HIIT to exhaustion improve significantly VO2max and anaerobic power irrespective of training intensity (29). However, the knowledge about concurrent cerebrovascular adaptations specific to HIIT conducted at different training intensities remains limited in healthy humans (23).…”
Section: Introductionmentioning
confidence: 99%